Development of an IoT-based monitoring system for preventing oil spills in single-phase transformers within rural distribution grids in Peru - Martinez Balbin, Luis (2025)
The paper describes developing an innovative monitoring system based on the Internet of Things (IoT) aimed at single - phase distribution transformers of rural type. These types of transformers are threatened by adverse weather conditions in conjunction with the increasing energy demand, which puts them at high risk of overheating, overloading, and other operational eventualities that could ultimately lead to a highly polluting oil spill. The proposal incorporates a single - phase energy meter PZEM - 004T, capable of measuring in real time. I t also includes an infrared sensor , MLX90614, for continuous surface temperature monitoring . For its part, the available A9G communication module makes it possible to have fluid communication with a central IoT platform, in addition to allowing the visuali zation and geopositioning in real time of the transformers at risk and the proactive control of the infrastructure. The experimental results show the accurate and timely diagnosis of overload and overheating, thus enunciating the easy creation of alerts to improve intervention and prevent failure. This effectively means that the proposed approach improves transformers' operational safety and reliability in rural areas and lays the foundation for future developments in electrical infrastructure management us ing IoT technologies.